STUDY ON ANTIGENOTOXIC EFFECTS OF MOROCCAN MEDICINAL PLANTS AND SPICES USING THE WHITE/WHITEP+ SOMATIC ASSAY IN DROSOPHILA - Mezzoug, N.; Abrini, J.; Serano, A. M.; Alonso-Moraga, A.; Idaomar, M. (African Journal of Traditional, Complementary and Alternative Medicines, 2006)
The antigenotoxic action of a selection of medicinal plants and spices from Morocco including laurel (Laurus nobilis), rosemary (Rosmarinus officinalis), verbena (Verbena triphylla), fenugreek (Trigonella foenum-graecum) and nutmeg (Myristica fragrens) was assessed using the eye white/whiteP+P (w/wP+P) Somatic Mutation and Recombination Test (SMART) assay of Drosophila melanogaster. Methyl methanesulfonate (MMS) was used as a positive mutagenic compound inducing high frequencies of spots in Drosophila larvae. The frequencies of spots per eyes of a treated series are compared to those of its concurrent positive control series using P2P- test for evaluation of the antigenotoxic effect. The nutmeg at 1% (w/v) demonstrated a marked decrease in MMS-induced spots with an inhibition rate of 50%. Rosemary, fenugreek seeds and laurel showed different inhibition rates with different level of significance.